Investigation of vacuum-integrated switchable polymer dispersed liquid crystal glazing for smart window application for less energy-hungry building. (15th February 2023) - Ghosh, Aritra
Abstract: The presence of more than one transparency and controllable intermediate transmission between ON and OFF states make the switchable smart glazing more attractive for less energy-hungry building integration than a static transparent window. However, to enable this switchable glazing for cold climatic buildings, overall heat transfer through the glazing needs to be reduced. In this work, the thermal and optical performance of integrated polymer dispersed liquid crystal and low heat loss transparent vacuum glazing was investigated using indoor characterisation. Two systems were developed where PDLC glazing was sandwiched between a vacuum and one acrylic sheet (Vacuum-PDLCA ) and vacuum and glass (Vacuum-PDLCG ). The employment of acrylic sheets reduced 21% of the overall weight of the system which made it suitable for retrofit building integration. Use of acrylic reduced 35% of solar transmission of PDLC ON state compared to the use of glass. Overall heat transfer coefficient ( U -value) or thermal transmittance was below 1.1 W/m 2 K for all Vacuum -PDLCG and Vacuum-PDLCA ON and OFF states. Solar heat gain coefficient or solar energy transmittance was highest at 0.45 for the Vacuum-PDLCG ON state and lowest at 0.23 for the Vacuum-PDLCA OFF state. Highlights: Vacuum-PDLCA was 21% lower weight than Vacuum-PDLCG . The overall heat transfer coefficient was lower than 1.1 W/m 2 K for all system. Solar heat gain coefficient of Vacuum-PDLCG ON and OFF states were 0.45 and 0.29 Solar heat gain coefficient of Vacuum-PDLCA ON and OFF states were 0.32 and 0.23 For warm climates Vacuum-PDLCA is suitable.